Residential Belonging: Examining the Impacts of Residential Learning Communities on Student Outcomes - Clary, Brendan G. (My University, 2018)
The purpose of this study is to determine if Residential Learning Communities at Kansas State University have a higher sense of belonging than their general education counterparts. Learning communities are used across the country and Kansas State University’s Residential CAT Communities, henceforth called RCAT, will be used as a typical example of a residential learning community. As many colleges have turned to residential learning communities to increase retention, performance, and happiness several studies have taken place delving into the outcomes these support structures create. The term learning community has been hotly debated, as “different observers have different views of what other specific primary components make a true, positive, healthy community that enables optimum learning to occur” but for the purposes of this project, residential learning community shall be defined as a group of students that live and learn together (Lenning & Ebbers 1999). We hope to answer what difference do residential learning communities make on the social belonging of college students? We also plan to study the academic results of learning communities asking: What outcome does belonging to a residential learning community have on the academic performance of college students.